Apoptosis-mediated antitumor activity of the ethanolic extract of Calotropis procera flowers: in vitro testing on the MG63 human osteosarcoma cell line - Alryahi, Israa Abd; Mohammed, Fadia Hameed; N. Al-Saily, Hala M. (Pharmakeftiki, 2025)
Developing cancer therapeutics that selectively target malignant cells without harming healthy tissue or encountering resistance remains a central challenge in oncology. This study aimed at evaluating the effects of an ethanol (70%) extract of Calotropis procera L. flowers on the osteosarcoma MG63 cell line. Following serial dilution, the extract was assessed by using a multi-parameter cytotoxicity assay in order to measure cell viability (valid cell count), total nuclear intensity, mitochondrial membrane potential, cell membrane permeability, and cytochrome c release. These parameters were analysed via high-content screening (HCS) in order to determine the extract’s therapeutic potential. The HCS results demonstrated that treatment with 200 μg/mL of the Calotropis procera flower extract can produce a highly significant effect across all five of the aforementioned parameters in MG63 cells.